Pengaruh Beban Kerja dan Komunikasi Terhadap Semangat Kerja Karyawan pada CV Mahlan Sila Nggembe Kecamatan Bolo (Jurnal Riset Manajemen dan Akuntansi, 2025)
This study aims to determine the significant effect of workload and communication on employee morale at CV Mahlan Sila Nggembe Kec, Bolo. This study is included in the category of Associative research. The population in this study used all employees at CV Mahlan, totaling 32 employees. The research technique used was saturation sampling, the research sample used was all employees of CV Mahlan, totaling 32 employees. The instrument in this study was a questionnaire with a Likert scale. Observation data collection techniques, Questionnaires, Literature studies. Data analysis techniques used validity tests, reliability tests and simple linear regression tests, then processed using SPSS for windows 23. The results of this study are that 1) Workload has a significant partial effect on Employee Morale at CV Mahlan Sila Nggembe. 2) Communication has a significant partial effect on Employee Morale at CV Mahlan Sila Nggembe. 3) Workload and Communication have a significant simultaneous effect on Employee Morale at CV Mahlan Sila Nggembe.